Cabin Safety Knowledge dan Perilaku Penumpang Penerbangan Low Cost Carrier - Maria Indriani Lumba; Felicia Anggriani; Devi Destiani Andilas; Siska Amonalisa Silalahi (Institut Transportasi dan Logistik Trisakti, 2021)
The aim of this research is to determine the effect of cabin safety knowledge on cabin safety behavior, and the role of cabin safety information source credibility as a variable that reinforces the influence of cabin safety knowledge on cabin safety behavior. This research is quantitative and uses a sample of 175 respondents surveyed by distributing online questionnaires via Google Form. The object of research is Lion Air passengers during the vulnerable period 2019 - 2020. This research uses the Partial Least Square (PLS) method. The results of this research indicate that cabin safety knowledge has a positive effect on cabin safety behavior, and the moderating effect test on cabin safety information source credibility is to strengthen the influence of cabin safety knowledge on cabin safety behavior.